2019
DOI: 10.1002/ets2.12269
|View full text |Cite
|
Sign up to set email alerts
|

SARA Reading Components Tests, RISE Forms: Technical Adequacy and Test Design, 3rd Edition

Abstract: In this research report, we describe the conceptual foundation and measurement properties of the Reading Inventory and Scholastic Evaluation (RISE). The RISE is a 6‐subtest, Web‐administered reading skills components battery. We review the theoretical and empirical foundations of each subtest in the battery, as well as item designs. The results included in this report feature a calibrated item pool based on a national sample of students, an extension of the vertical scale to span Grades 3–12, psychometric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…This is a confirmation of the internal validity of the algorithm. Evidence of external validity was also confirmed in analyses of learning gains on comprehension skills that were measured by independent psychometric tests ( Woodcock et al, 2007 ; Foorman et al, 2017 ; Sabatini et al, 2019 ). Learning gains on these tests were predicted by the accuracy rate of engaged question-answer observations in AutoTutor but not the disengaged observations.…”
Section: Discussion and Summarymentioning
confidence: 89%
See 1 more Smart Citation
“…This is a confirmation of the internal validity of the algorithm. Evidence of external validity was also confirmed in analyses of learning gains on comprehension skills that were measured by independent psychometric tests ( Woodcock et al, 2007 ; Foorman et al, 2017 ; Sabatini et al, 2019 ). Learning gains on these tests were predicted by the accuracy rate of engaged question-answer observations in AutoTutor but not the disengaged observations.…”
Section: Discussion and Summarymentioning
confidence: 89%
“…As an independent evaluation, learning gains were analyzed on subsets of the 252 students who took three standardized tests of comprehension before and after the larger CSAL AutoTutor intervention that included AutoTutor-ARC lessons. Of the 252 participants, 205 took both pre- and post-test of the Woodcock Johnson III Passage Comprehension subtest ( Woodcock et al, 2007 ); 143 took Reading Assessment for Prescriptive Instructional Data (RAPID) Passage Comprehension subtest develop by Lexia Learning ( Foorman et al, 2017 ) and 142 took Reading Inventory and Scholastic Evaluation (RISE) battery developed by ETS ( Sabatini et al, 2019 ). Fang et al reported that the learning gains in Woodcock Johnson and RAPID tests were highest for conscientious readers, lowest for struggling readers, with higher performing readers and under-engaged readers in between (Fang et al, submitted).…”
Section: Methodsmentioning
confidence: 99%
“…The real data were obtained from a web‐administered assessment of the Reading Inventory and Scholastic Evaluation (RISE; Sabatini et al., 2019). The RISE is a measure of six foundational reading skills.…”
Section: Relationship Of Mirt and Locally Dependent Irtmentioning
confidence: 99%
“…While only one month of treatment did result in small gains for certain component literacy skills, lengthier interventions would likely have led to greater treatment outcomes. Finally, the current standardized assessments of morphology (e.g., Foorman, Petscher & Bishop, 2012;Sabatini, O'Reilly, Halderman & Bruce, 2014;Sabatini, Bruce, Steinberg & Weeks, 2015) were not available at the time of the study.…”
Section: Limitationsmentioning
confidence: 99%